WORKPLACE SPIRITUALITY AND JOB CRAFTING: EFFORTS TO ELIMINATE THE IMPACT OF WORK OVERLOAD - A. Khoirul Anam; Anna Widiastuti; Fathur Rofiq (Journal of Management and Entrepreneurship Research, 2020)
Objective: This study discusses the importance of job crafting and workplace spirituality on the impact of role overload, which in turn leads to increase job performance. There is a limited previous research on job crafting and workplace spirituality, especially in the microfinance institutions. Research Design & Methods: Our research seeks to gain further understanding of the overall work overload occurrence, so we choose samples from microfinance institutions that can be expected to show excessive roles because of character of their work that is frequently in high pressure. Data collected from 119 questionnaires were analyzed using PLS-SEM with SMART-PLS software. Findings: The results showed that employees experienced work overload of both quantitative overload (feeling of any more work than the available time allocation) and qualitative overload (sense that the work requires skills, abilities and knowledge beyond the capacity of the individual), yet failed to show the role of workplace spirituality as a moderating variable. Implications & Recommendations: Future research can be carried out at larger institutions or industries and a larger number of samples for the sake of generalization and work overload occurence related to certain industrial situations. Contribution & Value Added: Our main contributions lie on the proposition that job crafting and workplace spirituality play a role in eliminating the impact of work overload. This study reinforces role evidence of job crafting and workplace spirituality on the impact of role overload.